Prospective development of legal education in the field of health care as a guarantee of medical reform implementation in Ukraine - M. A. Anishchenko (Zaporozhye State Medical University, 2019)
The purpose of the research: explore legal issues and the need for professional growth of health care workers towards the formation of legal competencies in the context of medical reform in Ukraine, identify promising ways for the development of legal education in health care. Materials and methods: normative-legal base of Ukraine, method of analysis, method of synthesis, comparative-legal and structural-functional methods. Results. The need for further development of legal education for healthcare workers stems from a detailed analysis of the regulatory and legal acts of Ukraine regulating medical and pharmaceutical activities, in particular, the Constitution of Ukraine, the Criminal Code of Ukraine, the Code of Ukraine on Administrative Offenses, the Laws of Ukraine "Fundamentals of the Legislation of Ukraine on Health Care", "On State Financial Guarantees of Medical Care of the Population", "On Amendments to Certain Legislative Acts of Ukraine regarding the improvement of legislation on the activities of health care institutions", "On the prevention of corruption", the decree of the Cabinet of Ministers of Ukraine "On approval of the competition for the position of head of state, municipal health care institutions", order of the Ministry of Health of Ukraine from 31.10.2018 № 1977 "On Amendments to the Handbook of qualification characteristics of workers occupations". Issue 78 "Health" and many others. Societies of public authorities, researchers, educators, medical, pharmaceutical workers and patients need to comprehend deeply the processes of modern transformation in the health sector, its legal regulation and the associated innovative approach to the competence matrix of the modern health worker, to develop a unified approach to the development of methods and forms of legal education in health care. Conclusions. In order to improve the effectiveness of legal education, it is necessary to develop and approve by the Resolution of the Cabinet of Ministers of Ukraine the National Concept for the Development of Legal Education in Healthcare, which should cover all subjects of legal relations in health care, including public authorities and local government, to provide the development of departments and pharmaceutical-legal and medical-legal teaching not only in medical and pharmaceutical, but also legal higher education institutions; a significant legal component of the training of health managers in master's programs; a mandatory component of medical, pharmaceutical and legal education for professionals and specialists in the field of health care at various levels and specialties. Anti-corruption education in the framework of continuing professional development of specialists should be a mandatory separate area of legal education.